Understanding Complexity: the Curvilinear Relationship Between Environmental Performance and Firm Performance - Ramanathan, Ramakrishnan (Journal of business ethics, 2018)
The nature of the relationship between environmental performance (EP) and firm performance (FP) of corporations is a long standing and contentious issue in the literature. This study is intended to advance this debate by arguing for the existence of curvilinear relationship and empirically testing the same using survey data on UK manufacturing firms. FP is captured in terms of growth in sales and market share. Our results show evidence for a quadratic relationship—as firms improve their EP, they seem to achieve much higher levels of FP. These results are consistent with the resource-based view of a firm; as firms engage in EP activities, they are able to gain inimitable knowledge that helps in further learning to further improve performance. Based on our results, we suggest that new studies focus on strategies to extend the period of increasing returns and maximizing the benefits of the positive association between EP and FP.